Amelioration of Tissue Fibrosis by Toll‐like Receptor 4 Knockout in Murine Models of Systemic Sclerosis. Issue 1 (January 2015) - Takahashi, Takehiro; Asano, Yoshihide; Ichimura, Yohei; Toyama, Tetsuo; Taniguchi, Takashi; Noda, Shinji; Akamata, Kaname; Tada, Yayoi; Sugaya, Makoto; Kadono, Takafumi; Sato, Shinichi
<x xml:space="preserve">Abstract</x> Objective Bleomycin‐induced fibrosis and the tight skin (TSK/+) mouse are well‐established experimental murine models of human systemic sclerosis (SSc). Growing evidence has demonstrated the pivotal role of Toll‐like receptors (TLRs) in several autoimmune inflammatory diseases, including SSc. This study was undertaken to determine the role of TLR‐4 in the fibrotic processes in these murine models. Methods We generated a murine model of bleomycin‐induced SSc using TLR‐4−/− mice and TLR‐4−/−;TSK/+ mice. The mechanisms by which TLR‐4 contributes to pathologic tissue fibrosis were investigated in these 2 models by histologic examination, hydroxyproline assay, enzyme‐linked immunosorbent assay, real‐time polymerase chain reaction, and flow cytometry. Results Dermal and lung fibrosis was attenuated in bleomycin‐treated TLR‐4−/− mice compared with their wild‐type counterparts. Inflammatory cell infiltration, expression of various inflammatory cytokines, and pathologic angiogenesis induced by bleomycin treatment were suppressed with TLR‐4 deletion. Furthermore, the increased expression of interleukin‐6 (IL‐6) in fibroblasts, endothelial cells, and immune cells in response to bleomycin in vivo and to lipopolysaccharide in vitro was notably abrogated in the absence of TLR‐4. Moreover, TLR‐4 deletion was associated with alleviated B cell activation and skew toward a Th2/Th17 response against bleomycin treatment. Importantly, in TSK/+ mice, another SSc murine model, TLR‐4 abrogation attenuated hypodermal fibrosis. Conclusion These results indicate the pivotal contribution of TLR‐4 to the pathologic tissue fibrosis of SSc murine models. Our results indicate the critical role of TLR‐4 signaling in the development of tissue fibrosis, suggesting that biomolecular TLR‐4 targeting might be a potential therapeutic approach to SSc.